The Social Construction of 'Will/Freedom' (Воля) in Ukrainian Media Discourse: Implications for National Identity and Social Cohesion - Kostusiak, Nataliia; et al. (European Journal of Social Science Education and Research, 2026)
This study examines how the concept воля is socially constructed in contemporary Ukrainian wartime media discourse and how this discursive construction contributes to the formation of national identity and social cohesion. Moving beyond a purely linguistic perspective, the research conceptualizes media discourse as a communicative space in which collective meanings are produced, negotiated, and legitimized. The study is grounded in social constructionism and integrates media discourse studies with critical discourse analysis to explain how language participates in the construction of social reality. The empirical analysis combines functional-cognitive, pragmatic, linguostylistic, and discourse-analytical approaches to examine representations of воля lexeme and notion in Ukrainian media texts covering military, political, psychological, and socio-cultural dimensions of the Russian-Ukrainian war. Particular attention is paid to the semantic specificity of the Ukrainian lexeme воля, which encompasses both liberty/freedom and will (volition), enabling media discourse to connect individual agency with collective freedom within a unified symbolic framework. The findings demonstrate that wartime media transform воля notion into a socially shared symbolic resource through which democratic values, collective resilience, national identity, and social cohesion are continuously constructed and reproduced. The study further argues that the unique semantic structure of воля lexeme distinguishes Ukrainian wartime discourse from comparable Balkan media discourses, where freedom and individual will are generally lexicalized separately. By integrating linguistic analysis with the sociology of communication, the article demonstrates how culturally specific concepts become mechanisms for constructing collective identities under conditions of war.
Keywords: social constructionism; media discourse; national identity; social cohesion; critical discourse analysis; sociology of communication; wartime communication, media discourse, phrase, sentence, nomination, lexeme